2011
DOI: 10.2172/1050681
|View full text |Cite
|
Sign up to set email alerts
|

Embodied Energy and Off-Grid Lighting

Abstract: The Lumina Project includes an Off-Grid Lighting Technology Assessment activity to provide manufacturers, re-sellers, program managers, and policymakers with information to help ensure the delivery of products that maximize consumer acceptance and the market success of off-grid lighting solutions for the developing world. SummaryThe greenhouse gas (GHG) emissions from fuel-based lighting are substantial given the paltry levels of lighting service provided to users, leading to a great opportunity for GHG mitig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…In recent years, there has been a proliferation of companies introducing a wide range of pay-as-you-go (PAYG) products. Recent reports have identified nearly 30 PAYG companies offering off-grid energy products in at least 32 markets (Alstone et al 2015). These companies are commercializing products that range from solar lamps that could sell for USD $10-$60, to solar home systems that could sell starting at USD $200 and reach much higher prices (Winiecki and Kumar 2014).…”
Section: Research Setting and Datasupporting
confidence: 54%
See 1 more Smart Citation
“…In recent years, there has been a proliferation of companies introducing a wide range of pay-as-you-go (PAYG) products. Recent reports have identified nearly 30 PAYG companies offering off-grid energy products in at least 32 markets (Alstone et al 2015). These companies are commercializing products that range from solar lamps that could sell for USD $10-$60, to solar home systems that could sell starting at USD $200 and reach much higher prices (Winiecki and Kumar 2014).…”
Section: Research Setting and Datasupporting
confidence: 54%
“…Recent studies have shown that electrification rates can remain low even in territories with significant investments in nearby grid infrastructure (Lee et al 2016). In that context, many companies recently started commercializing off-grid energy products not only in Africa, but also in parts of Asia, Central America, and Latin America (Alstone et al 2015). These companies-which are introducing products that range from basic solar lamps to complete solar home systems-usually have very limited information about their customers beforehand, facing significant uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel there has been an expansion in new business models and deployment approaches, with private sector businesses and new organizations launching across a range of regional and economic contexts. Many in the developing world utilize newly ubiquitous information technology for micro-payments and coordination of their supply chains [26]. Recognizing the need for global coordination and support of this new framework for providing electricity everywhere, even in the absence of an electricity grid, a range of national and international institutional efforts have emerged as well that focus on policy, market transformation, regulatory frameworks, and other areas.…”
Section: Off-grid Energy Technology Deploymentmentioning
confidence: 99%
“…Although these studies do take into account important proxies for electricity demand such as other household expenditures, education, poverty, population density and urban vs. rural differences, they often fail to mention or incorporate energy transition theories, complementary infrastructure (presence of roads and trade centers for example), and consumption preferences. In Kenya in particular it has been shown that the main driver of household rural electrification is not desire for electricity per se, but the desire for connective appliances (TVs, radios, and more recently cellphones) [7][13] [21].…”
Section: Supply Side Literaturementioning
confidence: 99%